Media Canva: Learning Media Breakthrough for Student Learning Motivation - Hasna Husniyah; Imam Tabroni; Ilham Fauzi AZ; Ryan Apriansyah; Yunisa Azahra; Taufik Luthfi; Ahmad Fajar (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Science and technology is one of the things that becomes a reference that the times continue to experience development. Currently, science and technology has experienced many improvements, especially in the world of education. Utilization of science and technology in learning can be used as a medium for delivering learning information effectively and efficiently. One of them is the use of Canva media in the learning process. Which is expected to spur student motivation in learning, especially in PAI subjects. This study aims to determine the effectiveness of Canva media on students' learning motivation. This research is a quantitative research with quasy experimental method, pretest-posttest control-group design with data collection using a Likert scale learning motivation questionnaire. The research sample was fifth grade students at SDN Purwamekar consisting of one experimental class and one control class. The results showed that Canva media had a positive effect on increasing students' learning motivation in PAI subjects, especially in the subject matter of Let's Get to Know Rasulullah Ulul Azmi.